Enhancing EFL Speaking Fluency and Reducing Anxiety through Mobile-Assisted Language Learning - Marzuki, Abdul Gafur; Huriyah, Huriyah; Triassanti, Risa; Kencanawati, Dewi; M. Nur, Mohammad Djamil; Ulfah, Ulfah (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Mobile-assisted language learning (MALL) has emerged as an effective method for improving EFL learners’ speaking abilities while alleviating affective barriers such as fear. This study investigated the effects of a MALL intervention with adaptive feedback on speaking fluency and anxiety alleviation through an explanatory sequential mixed-methods approach. Quantitative results from pre- and post-tests indicated that learners in the MALL group greatly surpassed those in the control group, demonstrating marked improvements in speech rate, accuracy, and fluency, alongside diminished anxiety levels. Qualitative interviews underscored that attributes such as autonomous practice, flexibility, and fast feedback enhanced learners’ confidence and readiness to communicate. The amalgamation of quantitative and qualitative studies suggests that technology-mediated learning might concurrently enhance cognitive skill development and emotional preparedness. These findings enhance the theoretical amalgamation of self-regulated learning and emotional support frameworks in mobile speech training and provide practical guidance for the development of adaptable, learner-centered digital solutions. The study highlights MALL’s capacity to establish equitable and efficient learning environments that improve speaking proficiency and communicative confidence in EFL settings.